Perancangan Aplikasi Pencarian Jalur Terpendek Untuk Lokasi Toko Bangunan Di Kota Bogor Dengan Metode A* (A-Star) Berbasis Android - Erniyati Ambotang (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2017)
ABSTRACT AbstractDistribution is one of the most important thing in the business, especially delivery of goods by land transportation.  Determination of traffic path plays a critical role in the goods distribution.  The best transportation track path will help the business to minimize the shipping cost as well as a more efficient delivery time.  A designated algorithm or system is required to search for the shortest and the most optimal traffic path from various numbers of existing alternative pathways. Case study was carried out at PT. Tulu Atas; the company that their business activities is controlled by land transportation. A * algorithm is one pathfinding algorithm that uses the shortest distance estimation to achieve the goal and has a heuristic value that is used as the basis for consideration. A mobile application is developed and implemented on android operating system based on this study to determine the shortest traffic path. Keyword : the shortest path problem, A*(A-Star) algorithm, android operating system